2017
DOI: 10.1186/s13613-017-0238-9
|View full text |Cite
|
Sign up to set email alerts
|

Superior accuracy of mid-regional proadrenomedullin for mortality prediction in sepsis with varying levels of illness severity

Abstract: BackgroundThe use of novel sepsis biomarkers has increased in recent years. However, their prognostic value with respect to illness severity has not been explored. In this work, we examined the ability of mid-regional proadrenomedullin (MR-proADM) in predicting mortality in sepsis patients with different degrees of organ failure, compared to that of procalcitonin, C-reactive protein and lactate.MethodsThis was a two-centre prospective observational cohort, enrolling severe sepsis or septic shock patients admit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
71
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 26 publications
7
71
1
1
Order By: Relevance
“…Our results demonstrate that MR‐proADM was the biomarker independently associated with the largest number of organ failure types (five out of the six considered in the SOFA score). This probably explains why MR‐proADM was also the best biomarker predicting mortality, which is consistent with previous findings 28 . AUROC analysis evidenced that accuracy of MR‐proADM was the highest to detect cardiovascular and renal failure (with areas > 0.80 in both cases).…”
Section: Discussionsupporting
confidence: 90%
“…Our results demonstrate that MR‐proADM was the biomarker independently associated with the largest number of organ failure types (five out of the six considered in the SOFA score). This probably explains why MR‐proADM was also the best biomarker predicting mortality, which is consistent with previous findings 28 . AUROC analysis evidenced that accuracy of MR‐proADM was the highest to detect cardiovascular and renal failure (with areas > 0.80 in both cases).…”
Section: Discussionsupporting
confidence: 90%
“…The level of MR proADM in this study ranged from 0.74 to 36.6 nmol/L. This level tends to be higher compared to the results of the study conducted by Andaluz et al 4 . The difference in the level of MR proADM is caused by several possibilities.…”
Section: Discussioncontrasting
confidence: 73%
“…The half-life of MR proADM is longer than that of ADM since its half-life is 2-3 hours whereas the halflife of ADM is only 22 minutes. 4 When infection occurs, the endothelial layer of blood vessel is damaged. The damage to the endothelium will activate the nucleus factor kappa β (NF-kB) to synthesize ADM from MR proADM.…”
Section: Introductionmentioning
confidence: 99%
“…Elke et al [25] previously found differences in performance depending on whether the infecting agent consisted solely of Gram positive vs. negative bacteria, as well as highlighting the influence of prior surgical procedures in patients directly admitted onto the ICU. A further ICU study by Andaluz-Ojeda et al [2] in 326 patients with severe sepsis or septic shock, as well as that of Enguix-Armada [30] in 388 patients with septic shock, also found MR-proADM to have the highest predictive value compared to conventional biomarkers such as PCT, CRP and lactate, although interestingly, the greatest performance was found in patients with a lower degree of organ failure. Nevertheless, no subgroup analysis was performed in either study relating to location of infection development or prior surgical history.…”
Section: Discussionmentioning
confidence: 84%
“…A standardised set of defined criteria to aid in the early identification of sepsis therefore remains elusive, despite the established use of specific parameters in conditions such as myocardial infarction and pulmonary embolism [2]. Furthermore, the poor acceptance of previous [3] and current [4,5] definitions has led to significant debate concerning the most appropriate clinical criteria required to make an accurate diagnosis.…”
Section: Introductionmentioning
confidence: 99%